Szeged as Hinterland Between 1915–1917 - Tóth, István (City and War, 2022)
The article discusses six aspects, which identified the stability of hinterland. Beside the sparse bibliographical sources, it mostly uses primary archival sources like mayor documents of Szeged, council documents of Szeged and lord lieutenant documents of Szeged. Additionally, it uses Délmagyrország newspaper from the four daily newspapers of Szeged, which has more than 70 articles about the theme, that can reflect the daily life of during the period. It handles all topics properly in proportion and in importance. It describes in the ways of catering provisions of grain, flour, meat and eggs. In the theme of military aid takes a look to the value of sacrifice on this the donate skills in the city. It discusses another important topic as well, the situation of women and children who went to the factories after the men marched into the army and specifically what happened with the factories. The second major part of the article are the finance, the public security and the health care. The finance and the public security are good evidence of the well managed background of the city’s needs. Inside of the health care is really important factor the ordinary health situation, defense against epidemics and activity of the field hospitals. As attachments and imagery, I tried to insert the archival documents, posters, pictures of the Móra Ferenc Museum which are connected with this theme and term.